TRANSFORMASI DESAIN SEBAGAI STUDI TIPOLOGI RUMAH BA’ANJUNG DAN BALLA - Fermanto Lianto; Denny Husin; Rudy Trisno (Jurnal Arsitektur ARCADE, 2025)
The phenomenon of the Indonesian capital relocation has shifted the development focus from Java Island towards the central part of Indonesia. The islands of Kalimantan and Sulawesi are preparing to carry out an entirely new planned city, including the modernization of these two islands, while their current condition is relatively traditional. The problem includes marginalized, threatened, eroded local culture and natural environment as the move would have grave repercussions for the entire region, such as deforestation, global cultural influences, and instantaneous modernization. Conservation and preservation of local architectural DNA have become urgent research; this paper presents a design idea as a study based on two representatives’ local architecture. The research objective is to study the various potency of two tribal houses' typological transformation, they are called Ba’anjung (Kalimantan) and Balla (Sulawesi), as alternative variations to embrace modernized tradition. It aims to promote its genetic structure as the arch-type for present-day development. Typology is utilized to study morphological formations, demonstrating the design process while investigating the two-house types as the case studies. Research steps include 1) Typological study, 2) Module Configuration, and 3) Design transformation. The outcome is a typo-morphological study based on unit design transformation. The novelty is a unit variation of forms Ba’anjung and Balla.